A Novel Colorimetric Nano Aptasensor for Ultrasensitive Detection of Aflatoxin B1 Based on the Exonuclease III-Assisted Signal Amplification Approach - Yu Chen (MDPI AG, 2021)
The detection of aflatoxin B1 (AFB1) has recently garnered much attention on the issue of food safety. In this study, a novel and sensitive aptasensor towards AFB1 is proposed using an Exonuclease III (Exo III)-integrated signal amplification strategy. This reported sensing strategy is regulated by aptamer-functionalized nanobeads that can target AFB1; furthermore, complementary DNA (cDNA) strands can lock the immobilized aptamer strands, preventing the signal amplification function of Exo III in the absence of AFB1. The presence of AFB1 triggers the displacement of cDNA, which will then activate the Exo III-integrated signal amplification procedure, resulting in the generation of a guanine (G)-rich sequence to form a G-4/hemin DNAzyme, which can catalyze the substrate of ABTS to produce a green color. Using this method, a practical detection limit of 0.0032 ng/mL and a dynamic range of detection from 0.0032 to 50 ng/mL were obtained. Additionally, the practical application of the established sensing method for AFB1 in complex matrices was demonstrated through recovery experiments. The recovery rate and relative standard deviations (RSD) in three kinds of cereal samples ranged from 93.83% to 111.58%, and 0.82% to 7.20%, respectively, which were comparable with or better than previously reported methods.